Hirsutanol A Induces Apoptosis and Autophagy via Reactive Oxygen Species Accumulation in Breast Cancer MCF-7 Cells - Fen Yang; Wen-Dan Chen; Rong Deng; Dan-Dan Li; Ke-Wei Wu; Gong-Kan Feng; Hou-Jin Li; Xiao-Feng Zhu (Elsevier, 2012)
Hirsutanol A is a novel sesquiterpene compound purified from the marine fungus Chondrostereum sp in the coral Sarcophyton tortuosum. Our previous studies had demonstrated that hirsutanol A exerted potent cytotoxic effect in many kinds of cancer cell lines. Here, the anticancer molecular mechanisms of hirsutanol A were investigated in breast cancer MCF-7 cells. The results showed that hirsutanol A could inhibit cell proliferation, elevate reactive oxygen species (ROS) level, and induce apoptosis and autophagy. Co-treatment with the potent antioxidant agent N-acetyl-l-cysteine could effectively reverse the effect of enhanced ROS production, which in turn, reduces growth inhibition, apoptosis, and autophagy mediated by hirsutanol A. In addition, blocking autophagy by bafilomycin A1 or Atg7-siRNA could synergistically enhance the antiproliferative effect and apoptosis induced by hirsutanol A. These data suggested that hirsutanol A could induce apoptosis and autophagy via accumulation of ROS and co-treatment with an autophagy inhibitor could sensitize MCF-7 cells to hirsutanol A. Keywords:: hirsutanol A, apoptosis, autophagy, reactive oxygen species (ROS), breast cancer